Komparasi Hukum Acara Pembuktian E-Arbitration di Indonesia dengan Shenzhen, Cina - Pritayanti Dinar, I Gusti Agung Ayu Gita (Acta Comitas : Jurnal Hukum Kenotariatan, 2021)
Online dispute resolution (ODR) is designed to facilitate the proceedings of parties dispute through online technology media such as PCSs, laptops and cell-phones. ODR is expected to facilitate an effective mediation, adjudication communication, so it can provide benefits in the form of time and cost efficiency in dispute resolution. The research questions investigated in this study are: (i) What are the advantages of the concept of proceedings by e-arbitration? (ii) Does the e-arbitration evidence collection procedure in accordance with the evidence principles of civil procedure law? This study employs the normative legal research method. The theories applied in investigating the problems in this research are the economic-legal theory and evidence principles. Through this study, it can be determined the comparison of procedure, benefit of e-arbitration evidence regulation in ShenZhen and Indonesia.